EVALUASI KINERJA REKSADANA DAN KEBIJAKAN SUKU BUNGA: BUKTI EMPIRIS REKSADANA SAHAM DI INDONESIA - Pranyoto, Edi; -, Susanti (Jurnal Manajemen Magister Darmajaya, 2018)
Many investors have problems in choosing investment instruments with returns and risks in accordance with the wishes of investors. One investment that can be chosen by the investors is mutual funds. This study aims to evaluate the performance of stock mutual funds and determine the impact of interest rates on stock mutual funds. This research was carried out during 2013-2017. The analysis use Analysis Regression. The results of the analysis indicate that during 2013-2015 the performance of stock mutual funds was below the interest rate, but during 2016-2017 the performance of stock mutual funds fluctuated and several times outperformed interest rates. The test results show that the interest rate variable has a significant negative effect on Stock Mutual Funds. This shows that interest rates have a negative influence on the performance of stock mutual funds, this means that when the government increases interest rates, the performance of stock mutual funds decreases, and vice versa, when interest rates decrease, the performance of stock mutual funds increases. The cause of the reduction in net asset value of stock mutual funds in the short term when interest rates increase, due to an increase in interest rates makes the majority of people shift their funds from stock mutual funds to savings or time deposits.Keywords : Mutual Funds Performance, Interest Rate.